2020
DOI: 10.29252/ieepj.2.3.148
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lights and Colors on the Environmental Perception and Legibility Using Augmented Reality Technology

Abstract: One's cognitive perception of the environs is in direct relationship with their subjective mental image of the surroundings. Various elements influence the perception and legibility of the environment before human mind. Among these elements are the light and color of the environs. The question is which light or color spectrum is capable of heightening the legibility and spatial perception of the given environment for users. Considering that, the aim of the present study is first to examine the effect of lights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…Ashwini Sunil Nair studied the effect of light colors in the built environment on the behavior of children with autism using many neutral tones, and pastel shades proved to be autism-friendly with a sedative and soothing effect, whereas bright, bold and strong colors resulted in behavioral changes in children with autism, who are prone to be sensitive to light [64]. Ahmadreza Khalili used augmented reality to simulate various environments based on different light and color parameters and found that neutral colors were more attractive than others in two-color spaces [65].…”
Section: Emotional Responses To Colored Light In Spacesmentioning
confidence: 99%
“…Ashwini Sunil Nair studied the effect of light colors in the built environment on the behavior of children with autism using many neutral tones, and pastel shades proved to be autism-friendly with a sedative and soothing effect, whereas bright, bold and strong colors resulted in behavioral changes in children with autism, who are prone to be sensitive to light [64]. Ahmadreza Khalili used augmented reality to simulate various environments based on different light and color parameters and found that neutral colors were more attractive than others in two-color spaces [65].…”
Section: Emotional Responses To Colored Light In Spacesmentioning
confidence: 99%